Fermentation Extract of Naringenin Increases the Expression of Estrogenic Receptor β and Modulates Genes Related to the p53 Signalling Pathway, miR-200c and miR-141 in Human Colon Cancer Cells Exposed to BPA - Sara Julietta Lozano-Herrera; Gabriel Luna-Bárcenas; Ramón Gerardo Guevara-González; Rocio Campos-Vega; Juan Carlos Solís-Sáinz; Ana Gabriela Hernández-Puga; Haydé Azeneth Vergara-Castañeda (Molecules, 2022)
The estrogenic receptor beta (ERβ) protects against carcinogenesis by stimulating apoptosis. Bisphenol A (BPA) is related to promoting cancer, and naringenin has chemoprotective activities both can bind to ERβ. Naringenin in the colon is metabolized by the microbiota. Cancer involves genetic and epigenetic mechanisms, including miRNAs. The objective of the present study was to evaluate the co-exposure effect of colonic in vitro fermented extract of naringenin (FEN) and BPA, to elucidate molecular effects in HT-29 colon cancer cell line. For this, we quantified genes related to the p53 signaling pathway as well as ERβ, miR-200c, and miR-141. As an important result, naringenin (IC50 250 µM) and FEN (IC50 37%) promoted intrinsic pathways of apoptosis through phosphatase and tensin homolog (PTEN) (+2.70, +1.72-fold, respectively) and CASP9 (+3.99, +2.03-fold, respectively) expression. BPA decreased the expression of PTEN (−3.46-fold) gene regulated by miR-200. We suggest that once co-exposed, cells undergo a greater stress forcing them to mediate other extrinsic apoptosis mechanisms associated with death domain FASL. In turn, these findings are related to the increase of ERβ (5.3-fold with naringenin and 13.67-fold with FEN) gene expression, important in the inhibition of carcinogenic development.